Metaphor in the productions of Tsunit Fattal The novel "The Pictures on the Wall" for example - Nasir, Mariam Hasan; Abdul Karim, Qusay Nabil (Al-Adab Journal, 2022)
This research sheds light on one of the semantic phenomena in the Hebrew language, which is the metaphor. This semantic phenomenon was dealt with in one of the modern Hebrew novels, namely, the novel "Pictures on the Wall" by the Jewish writer of Iraqi origin, Tsunit Fattal. The events of this novel revolve around a Jewish girl named Nuria who lived in Baghdad with her family in the first half of the last century.This research deals with the concept of metaphor and its sources in the novel "Pictures on the Wall" through selected examples of the novel, as the most important events of this novel were identified through these models. The research concluded that the author employed the many metaphors that she used in her novel in order to describe many different events, characters and their characteristics, and in order to attract the reader's attention to the conditions of the Jews in Iraq during that period. She was also able to enrich her novel with new and varied words from different semantic fields that showed us the vast amount of the writer's linguistic storage.